David Cronenberg's Videodrome - Shore, Howard 1946- (<<The>> Criterion Coll., 2004)
"Der Präsident einer Kabelfernsehgesellschaft stößt auf ein Videoprogramm, das Halluzinationen erzeugt, den Sinn für Realität und Illusion verschwinden läßt und zu einem Gehirntumor anwächst. In der Folge verwandelt er sich in eine lebende Videokassette. Horror- und Science-Fiction-Thriller mit Ekel- und Schockbildern, der als grimmige schwarze Komödie moderne Medien-Technologien weiterdenkt. Im Gesamtwerk des Regisseurs David Cronenberg markiert der Film den Wendepunkt zur Phase des subtileren Horrors." [film-dienst.de]
Orig.:
Bildformat 1.85:1 (16:9). - New, restored high-definition digital transfer
Orig.: Kanada 1982
Enth. two audio commentaries: David Cronenberg and director of photography Mark Irwin, and actors James Woods and Deborah Harry ; "Forging the new flesh", a new half-hour documentary featurette by filmmaker Michael Lennick about the creation of "Videodrome's" video and prosthetic makeup effects ; "Effects men", a new audio interview with special makeup effects creator Baker and video effects supervisor Lennick ; bootleg video: The complete footage of "Samurai Dreams" and seven minutes of transmission from "Videodrome", presented in their original, unedited form with filmmaker commentary ; original theatrical trailers and promotional featurette ; stills galleries featuring hundreds of rare behind-the-scenes production photos, special effects makeup tests, and publicity photos
Keywords: Pornografie; Metamorphose; Realitätsverlust; Fernsehsendung; Fernsehproduzent; Videorecorder; Fiktionale Darstellung; DVD-Video